The red scrolls of magic - Clare, Cassandra; Chu, Wesley (New York : Margaret K. McElderry Books, 2019)
High Warlock Magnus Bane learns that a demon-worshipping cult, the Crimson Hand, is wreaking havoc across Europe, threatening more than just his romantic getaway with new boyfriend, Alec Lightwood.
Keywords: Warlocks -- Fiction; Magic -- Fiction; Fantasy fiction